Pengaruh Problem Based Learning Terhadap Kemampuan Literasi Matematis Siswa Kelas VII Di SMP Negeri 1 Bobotsari - Ajie Dina Kis Puji Astuti (AlphaMath : Journal of Mathematics Education, 2018)
The research aimed to study the effect of Problem Based Learning towards the  student’s mathematical literacy skills. This research is an experimental research. The design of this research used post-test-only control design. The population of this research were the whole students on the seventh grade of SMP Negeri 1 Bobotsari. Sampling in this research used cluster random sampling and obtained VII B grade as an experimental class and VII D grade as an control class. The data were collected using mathematical literacy skill test in the form of essay. The results of mathematical literacy skill test on experiment class showed that the average score was 77,81 and the average score on control class was 69,19. After testing the hypothesis was tested using independent sample t-test , a significance value of 0,0115 was obtained, with significance value or α = 0,05. It was concluded that Problem Based Learning was effective toward grade VII student’s mathematical literacy skill in SMP Negeri 1 Bobotsari.